Congenital Symmastia: A Four-Step, Minimally Invasive Approach - Neha Jain; Uthraa Thambiran; Leena Jain; Siddharth Prakash; Shrirang Purohit; Samir Kumta (Indian Journal of Plastic Surgery)
Symmastia is a rare condition in which breasts are unified medially due to aberrant development of mammary tissue in the intermammary region, resulting in the appearance of an intermammary web. There are limited reports on this rare anomaly and hence, no standard protocols on its management. Additionally, creating a normal cleavage in these young patients without scars over or around the breast is a challenge from an esthetic standpoint. In this article, we present a case of congenital symmastia corrected by four steps: liposuction of the intermammary region, use of suction drains along medial breast border, transdermal bolster sutures, and customized compression garment. Esthetic creation of the medial breast footprint and good preservation of breast contours was achieved with considerably less scars. Thus, we propose our four-step approach as an effective, minimally invasive method for treating congenital symmastia.